Digital Transformation & COVID-19: the Case of Greece - Vratimos, Achillefs (European Scientific Journal, ESJ, 2022)
The impact of the COVID-19 pandemic has caused significant problems to many different public sector functions worldwide extending further than just public health. To protect citizens and keep services functional, the digital transformation of the public sector was selected by many countries as the most reliable solution, a policy with the goal of servicing citizens on time and efficiently. Following the examples of other countries, Greece also moved in the same direction, successfully managing to respond to the strict demand times and implement many digital services such as Gov. gr, a central platform for public administration information and services, the digital platform myDeskLive.gov.gr for remotely serving citizens and businesses by conducting digital appointments and the creation of the Paperless Prescription Service. These are prime examples of how successful this transition has been for Greece, considering how far behind it was lagging compared to other advanced countries, and the progress made in such a short period of time. This paper presents in detail the innovative applications implemented by Greece in the context of combating and limiting the effects of the COVID-19 pandemic supported by statistics that reflect the spread use of these applications.